Comparison of Acute and Chronic Toxicity Laboratory Bioassay Endpoints with Benthic Community Responses in Field‐Exposed Contaminated Sediments. (30th July 2019) - Moore, David W.; Farrar, Daniel; Altman, Safra; Bridges, Todd S.
Abstract: Sediment toxicity is usually assessed by conducting laboratory bioassays on thoroughly homogenized, field‐collected, sediment samples. Although it is generally held that these bioassays provide a conservative assessment of the potential for environmental impact, there are few studies comparing the results of laboratory sediment bioassays with actual measures of benthic community health in exposed field populations. To help inform an understanding of the relative efficacy of laboratory‐based bioassays in predicting potential impacts in exposed field populations, a laboratory‐to‐field comparison study was conducted. Laboratory bioassays included standard 10‐d acute toxicity tests measuring survival in 4 species of estuarine/marine amphipods ( Eohaustorius estuarius, Ampelisca abdita, Rhepoxinius abronius, and Leptocheirus plumulosus ) and 2 longer term, 28‐d sublethal tests with a marine polychaete, Neanthes arenaceodentata (survival and growth), and the amphipod L. plumulosus (survival, growth, and reproduction). A highly contaminated and toxic sediment was mixed with a cleaner sediment of similar grain size to produce a series of diluted contaminated sediment treatments (0, 6, 12, 25, and 50%). Sediment treatments were placed in containers and deployed in the field. At specified intervals (at time of deployment and 9 and 12 mo post deployment), containers were retrieved from the field and analyzed for sediment chemistry, infaunal community composition, and toxicity. Laboratory toxicity endpoints were compared with measures of benthic community health to evaluate the ability of the toxicity tests to accurately predict benthic impacts. The results of these comparisons indicate that the laboratory tests evaluated provide conservative estimates of potential benthic community impacts, with both acute and chronic tests detecting effects at lower treatment levels than were detected in exposed field populations using traditional measures of benthic community health. Environ Toxicol Chem 2019;38:1784–1802. Published 2019 Wiley Periodicals, Inc. on behalf of SETAC. This article is a US government work, and as such, is in the public domain in the United States of America.